2020
DOI: 10.1021/acs.jafc.0c04290
|View full text |Cite
|
Sign up to set email alerts
|

High-Dietary Fiber Intake Alleviates Antenatal Obesity-Induced Postpartum Depression: Roles of Gut Microbiota and Microbial Metabolite Short-chain Fatty Acid Involved

Abstract: Antenatal obesity increases the risk of postpartum depression. Previous research found that dietary fiber supplementation could alleviate mental behavioral disorders. The present study aims to uncover the effects of high-dietary fiber intake on high-fat diet (HFD)-induced depressive-like behaviors and its underlying mechanism. Female C57BL6/J mice were fed with HFD to establish an antenatal obese model. A high-dietary fiber intake (inulin, 0.037 g/kcal) significantly attenuated cognitive deficits and depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 81 publications
2
85
0
Order By: Relevance
“…The intake of prebiotics could regulate the production of gut microbial metabolites like SCFAs and bile acids thus influencing the metabolic process [ 94 ]. It has been reported that the administration of isomaltodextrin was positively related to the concentrations of acetic and butyric acids in mice with glucometabolic disorder [ 38 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…The intake of prebiotics could regulate the production of gut microbial metabolites like SCFAs and bile acids thus influencing the metabolic process [ 94 ]. It has been reported that the administration of isomaltodextrin was positively related to the concentrations of acetic and butyric acids in mice with glucometabolic disorder [ 38 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…Interestingly, the genus Lactobacillus (Lactobacillales order, Lactobacillaceae family) was significantly decreased in diabetic mice, while treatment with FLRB increased it by approximately eightfold, which was much higher than it was in NC mice ( Figure 5B and Supplementary Table 3 ). Lactobacillus is known for its probiotic roles in food consumption, which could modify abnormalities in intestinal microbes and retard hyperglycemia ( Liu Z. G. et al, 2020 ). Moreover, Lactobacillus was also demonstrated to be obviously associated with butyrate levels ( Sun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, our study was the first direct evidence to show that the relative abundance of Dubosiella was highly enriched in FLRB-treated diabetic mice. A previous study indicated that vitamin K2 supplementation could increase the abundance of intestinal Dubosiella and decrease the relative expression of activating transcription factor 4 to inhibit blood pressure in mice ( Liu T. H. et al, 2020 ). However, changes in Dubosiella in the intestine of diabetic mice have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…5-HT is a neurotransmitter synthesized from the degradation of amino acid, tryptophan, and plays a key role in regulating appetite, mood, sleep, and sexual function. A recent study provides evidence that high dietary fibre intake upregulates the expression of 5-HT and inhibits neuroinflammation [ 41 ]. In the gut, 5-HT is produced by E.coli , Streptococcus sp., and Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%